A Brumby Story : Dancing Brumby's Rainbow - Elyne Mitvhell (U.S.A, 1998)
Choopa, the blue-roan dwarf foal is a natural dancer and was trained as a Spanish dancing horse until he escaped and made his way back home to the beautiful snow country. Now Choopa must start fending off increasing attacks from Old Strawberry, the herd leader. Choopa?interest is sparked by rumours of a tiny dwarf filly that is the prize of Old Strawberry?herd. Ages 10+
Keywords: Fiction